2018
DOI: 10.4103/ua.ua_109_17
|View full text |Cite
|
Sign up to set email alerts
|

Organ preservation in leiomyosarcoma bladder: Case report and review of literature

Abstract: Leiomyosarcomas (LMSs) account for <0.1% of all bladder malignancies. Due to the infrequent occurrence of these tumors, established guidelines for management are lacking. Conventionally, radical extirpative surgery has been advocated. We present our experience with organ preservation in a young male presenting with LMS bladder. A brief review of literature supporting organ preservation in selected cases has also been presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…From a pathological point of view, the different publications suggest the use of three main histological and prognostic classifications: the NCI, FNCLCC and Mayo LMS-UB grading system which take into consideration the degree of differentiation, mitosis number (per 10 CFG), necrosis and nuclear atypia [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a pathological point of view, the different publications suggest the use of three main histological and prognostic classifications: the NCI, FNCLCC and Mayo LMS-UB grading system which take into consideration the degree of differentiation, mitosis number (per 10 CFG), necrosis and nuclear atypia [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, adjuvant chemotherapy was indicated in one case but refused by the patient. Radical cystectomy surgery is most commonly recommended, while partial cystectomy is used for small tumours and patients refusing radical treatment [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the relationship between long-term chemotherapy of cyclophosphamide and bladder sarcoma, and a minority reports have revealed this point. Apart of above mentioned, the presence of urinary bladder diverticulum, abuse use of ketamine, 3 and radiation exposure, 4 could be a contribution of risk factor to this rarity. We could not discern any those factors, while our patient had a history of smoking and type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Обсуждение Неуротелиальные опухоли составляют менее 5 % всех злокачественных новообразований мочевого пу зыря [1]. При этом ЛМС является крайне редкой опу холью мочевого пузыря, встречающейся менее чем в 0,1 % случаев и развивающейся в собственно мышеч ном слое мочевого пузыря [2]. Первый случай обнару жения ЛМС мочевого пузыря был представлен в 1946 г. W. Baurys и R.R.…”
Section: после повторного консультирования онкологами рекомендован сл...unclassified